Comparison of strengthening methods for tubular T joint corresponding to each static failure mode. (February 2022) - Zafimandimby, Mampiandra N.H.; Liu, Yongjian; Yan, Biao; Jiang, Lei; Ma, Yinping
Abstract: This paper is aimed to determine the optimal strengthening method for hollow section T-joint under compression based on the comparison of the increase on strength, self-weight, constructability and aesthetic. Numerical research is carried out to compare each type of strengthening method from its strength efficiency. Increase of strengthened joint self-weight is calculated as the self-weight of the strengthening. It affects the overall weight of the structure and the economy. Possibility of strengthening in time, welding difficulty and visual sensibility are the analyzed parameters in the constructability and aesthetic analysis. For the chord face failure mode, method mainly consists on strengthening the chord flange with material. Four types are proposed in which the collar plate strengthening is the optimal type with ponderation equal to 11.75 for all the criteria combined. The brace failure mode is reduced or avoided through adding material to link the chord and the brace member or to weld the brace together with the chord member. The collar plate strengthening is the optimal among the four types proposed for β ≤ 0.8 and the integral joint for β = 1 which is the most frequent in bridge. The sidewall plate is the only type of strengthening to avoid or reduce the sidewall failure.